Training by the PUPIK Team, FMIPA UNP Biology Laboratory, on Making Nata De Coco and Production Quality Testing During the Storage Process - putri, dwi hilda; Advinda, Linda; Irdawati, Irdawati; Fevria, Resti; Chatri, Moralita; rahmi, elva; Ghiffari, Muhammad; Viona, Alda (Fakultas MIPA Universitas Negeri Padang, 2023)
Nata de coco is one way to use coconut water waste that can no longer be used so that it can reduce environmental pollution. The quality of nata as a food and beverage product must be monitored. This article aims to analyze the shelf life of Nata de coco based on its shelf life. The work methods used include: 1) testing the durability of nata de coco at room temperature, and 2) testing the durability of nata de coco at cold temperatures or in the refrigerator. Organoleptic tests carried out included aroma, color, taste and texture. The results achieved show that nata de coco stored in the refrigerator can last four weeks, while those stored at room temperature can only last for one week